Enhancement of the FMN–heme interdomain electron transfer in neuronal nitric oxide synthase by heat shock protein 90 - Zheng, Huayu (FEBS Lett, 2020)
Purified dimeric human Hsp90α was used to investigate whether Hsp90 affects the FMN–heme interdomain electron transfer (IET), an essential step in nitric oxide synthase (NOS). The IET rate for rat neuronal NOS (nNOS) displayed a noticeable increase upon adding Hsp90 in a dose-saturable manner, and the effect was abolished by a single charge-neutralization mutation at conserved Hsp90 K585. The kinetic results with added Ficoll 70 further suggest that Hsp90 influences the IET through association with nNOS. The Hsp90 effect is presumably via narrowing the available conformational space for the FMN domain motions.